Priority Needs for Developing Teachers’ Mindfulness: A Case Study of a Medium-Sized Private School in The Western Region of Thailand - Wongsomboon, Chanikan; Kulopas, Dhirapat (Mahachula Academic Journal, 2026)
This research aimed to study the current state, desired state, and priority needs for developing teachers’ mindfulness at a medium-sized private school in the western region of Thailand. A descriptive research design was employed, with data collected from all 68 administrators and teachers using a questionnaire covering five mindfulness components across 36 items. The instrument demonstrated a scale-level Content Validity Index (S-CVI) of 0.99 and an overall Cronbach’s alpha coefficient of 0.96 Data were analyzed using mean, standard deviation, and the Modified Priority Needs Index (PNI modified). The findings revealed that the current state of teachers’ mindfulness was at a high level overall (mean = 3.947–4.053), while the desired state was at the highest level (mean = 4.553–4.605). Regarding priority needs at the component level, present-moment awareness ranked first (PNI = 0.160), followed by emotion regulation (PNI = 0.154), non-judgment (PNI = 0.151), self-awareness (PNI = 0.139), and compassion and empathy (PNI = 0.131), respectively. At the indicator level, the ability to refocus on work after being interrupted was identified as the highest priority need (PNI = 0.188). In terms of preferred development approaches, most teachers favored off-site activities led by external experts with follow-up support through Professional Learning Communities (PLC), within a time allocation of no more than one hour per session. Work-related stress was identified as the primary concern teachers most sought to address.